Research on Impact of Digital Currency Development on Transmission Mechanism of Monetary Policy - Chen, Xi (Asia Pacific Economic and Management Review, 2026)
Driven by the global wave of financial technology, digital currencies represented by central bank digital currencies are moving from theoretical concepts to practical explorations, indicating a potential paradigm shift in the global monetary system. This shift poses a fundamental challenge to the core of modern macroeconomic regulation. In this context, this study focuses on central bank digital currencies (CBDCs) and systematically deconstructs how they trigger nonlinear changes in the transmission path of monetary policy through five classic channels: interest rates, credit, asset prices, exchange rates, and expectations. This study found that digital currency has profoundly changed the transmission efficiency, boundary of action, and feedback loop of monetary policy through three core mechanisms - reshaping the financial intermediary pattern, creating new policy tool combinations, and constructing high-dimensional real-time data fields. The programmability of CBDC, layered interest rate design, and potential breakthroughs in the lower bound of zero interest rates provide space for monetary policy.